IMPROVING MUNICIPAL MANAGEMENT ASSOCIATED WITH THE RESOURCES COLLECTION THROUGH IT: CAASIM CASE IN MEXICO - Antonio Alejandro Arriaga-Martinez; Sonia Ximena Diaz de Cossio-Priego (European Scientific Journal, ESJ, 2013)
The study presented is research based on the impact of the pay stub in the management of the Water Commission (CAASIM), an institution that works in some municipalities that belong to the state of Hidalgo in Mexico. Largely, the findings show significant changes such as reduced operating costs, increase in the amount of revenue, decrease in the volume of water consumed per household, reduced staff dedicated to bill collecting and the use of a convenience store as a principle payment point. The findings in this research, considering data over several years, completely refute the belief that people in Latin America are seeking to evade the payment of their obligations to the government, but that there is a need for more efficient administrative mechanisms in order to provide adequate service for citizens.